(3MUhd GdLHQ HbQGAI CHj YeQhs - (3YHO Gddg Hf Ydj Hf YHO GdQMef ShjOGf GdOedjLj,J (B1234 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdbQBf TaGA ddeDefjf hHYO SCdfi HYV GdCMHGH Cf CYed ebOeI ebOeI ai bQGAI GdEeGe CHj YeQh GdHUQi CMO GdSHYI GdCYdGe s
(3BNQgG (B:s
(3HeUjWQ HGdUGO hdjS dg JcHjQ ef BNQ GdVMi Edi GdJeGe hCSCd Gddg MSf GdNJGe hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3GdfSNI HgG MhGTs
(3HChdg fbhd hahGFOs
(3bQGAGJs
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B89s
Keywords: (3GdeLGejYs